Is the New Biology a Tool of Social Repression? - Ruse, Michael (The Hastings Center report, 1984)
Book reviewed in this article: Not In Our Genes: Biology, Ideology, and Human Nature. By R. C. Lewontin, Steven Rose, and Leon J. Kamin.